Selection and characterization of microseismic information about rock mass failure for rockburst warning in a deep tunnel. (January 2022) - Niu, Wenjing; Feng, Xia-Ting; Feng, Guangliang; Xiao, Yaxun; Yao, Zhibin; Zhang, Wei; Hu, Lei
Highlights: The failure behavior and microseismicity of rockbursts in tunnels were analyzed. Interference factors for rockburst warning were clarified. A selection method of MS information for rockburst warning was established. The crack initiation level and damage degree of rockbursts were characterized. Abstract: A rockburst is a complex dynamic engineering failure hazard encountered in deep tunnels, which leads to serious casualties, mechanical damage, project delays, and economic loss. To conduct microseismic (MS) warning and safety control of rockburst hazard can reduce the degree of damage and incidence of rockburst failure. Through analysis of the failure behavior and microseismicity of rockbursts of different intensities, the interference factors and causes for rockburst warning were clarified. By introducing the MS energy gradation curve to analyze the completeness of the MS catalogue, a selection method of MS information for rockburst warning was established. Geomechanical conditions, such as the crack initiation level and degree of damage of a rock mass with different intensities of rockbursts, were characterized by using the distribution of MS events based on a MS energy gradation curve. The logarithm of MS energy threshold value is 0.30 for screening MS events for rockburst warning in this tunnel was set. By comparing the difference of the slope of its straight-line segment, its d 90 value, and other parameters of MS energy gradation curve in the area at risk to the characteristic parameters used for rockburst warning of various intensities, whether the crack initiation level and degree of damage have reached the condition of occurrence of rockburst can be judged, which can provide some assistance and reference for rockburst warning. Relevant results have been applied in the follow-up rockburst warning work in a tunnel, showing a good effect. More than 85% of rockburst hazards can be effectively identified and warnings were issued. The method proposed here can provide support for warning of rockburst accuracy in the excavation of deep-buried hard rock tunnels.